ECG risk markers among premenopausal and postmenopausal SCD victims - Eskuri, M A E; Holmstrom, L; Vahatalo, J; Kentta, T V; Tikkanen, J; Pakanen, L; Perkiomaki, J; Huikuri, H V; Junttila, M J (Europace (London, England), 2024)
Abstract Background Majority of the SCD victims aged 50 years or younger are male. On average menopause occurs at the age of 51.4 years and it has a substantial role in cardiovascular risk burden among women. The mechanisms and risk markers of SCD are not as well defined for women as they are for men possible due to difference in population burden, and electrocardiographic risk markers do not seem to make a difference in this matter. Purpose The aim of this study was to determine electrocardiographic findings among women at pre- and postmenopausal age in a large SCD population. Methods The Fingesture study has systematically collected clinical and autopsy data from SCD victims in Northern Finland between 1998 and 2017. The cohort consists of 5,869 SCD victims of which 1,238 are women (21.1%). Antemortem electrocardiograms (ECG) were recorded in 1,101 subjects (women 25.3%). Women aged ≥ 52 years were considered as postmenopausal and ≤ 51 years old as premenopausal as the direct information of the menopause lacked due to the retrospective nature of this autopsy-based data. Results Only 7.9% of the female subjects experienced SCD under age of 52 years (P<0.001). No statistically significant differences in ECG abnormalities were found between pre- and postmenopausal women. However, almost one female SCD victim out of four lacked any ECG abnormalities in premortem ECG (26.3% of premenopausal and 24.2% of postmenopausal women, P=1.000). In general, ECG abnormalities were more prevalent in SCD victims at postmenopausal age. Though, fragmented QRS, particularly in the lateral ECG leads, was observed in 47.4% of women at premenopausal age group and in 42.1% of women at postmenopausal age even though statistical significance was not obtained (p=0.810). ECG-LVH, as per Cornell's criteria, was present in 4.8% of individuals in premenopausal age group whereas in postmenopausal age group, it was observed in 19.0% of subjects (P=0.140). ECG variables are presented in Table 1. When the analysis was repeated between the women <55 years of age and ≥55 years of age, only left ventricular hypertrophy (LVH; Cornell) was statistically significant and more common in women ≥55 years old (19.5% vs. 3.6%, P=0.037). Conclusion Premenopausal SCDs are rare. Approximately one female SCD victim out of four did not have any ECG abnormalities prior to SCD. Only ECG-LVH remained statistically significant in analysis between younger and older women, and was clearly more prevalent finding among postmenopausal SCD victims. Table 1